Aktivitas Antijamur Nanopartikel Zinc Oxide (ZnO) yang Disintesis Menggunakan Ekstrak Kulit Buah Duku (Lansium domesticum) - Mutiara Ihsani; Vera Estefania Kaban; Razoki Lubis (LPPM Universitas Abdurrab, 2026)
This study evaluated zinc oxide (ZnO) nanoparticles biosynthesized using an aqueous extract of duku (Lansium domesticum Corr Corr.) fruit peel for their antifungal activity against Candida albicans, given the rising incidence of candidiasis and the growing resistance to conventional antifungal drugs. The synthesized ZnO nanoparticles were characterized by particle size analysis, showing a Z-average diameter of 89 nm and a polydispersity index of 0.243, confirming their nanoscale dimension and reasonably uniform size distribution. Antifungal activity was assessed using the agar well diffusion method at concentrations of 25-500%. ZnO nanoparticles inhibited Candida albicans growth at every concentration tested, with inhibition zone diameters increasing proportionally with concentration, from 9.65 ± 0.28 mm (moderate category) at 25% to 15.33 ± 0.11 mm (strong category) at 500%, compared with 31.86 mm for the ketoconazole positive control. One-way ANOVA confirmed significant differences among treatment concentrations (F = 397.795; p < 0.001). These findings indicate that green-synthesized ZnO nanoparticles from duku peel extract exhibit concentration-dependent antifungal activity against Candida albicans , supporting their potential as an environmentally friendly alternative antifungal agent.